2022
DOI: 10.1155/2022/6170062
|View full text |Cite
|
Sign up to set email alerts
|

Pharmaceutical Care Service at Primary Health Care Centers: An Insight on Patient Satisfaction

Abstract: Background. Patient’s health care experiences and satisfaction are frequently used as a healthcare quality indicator. Aim. The study aims to evaluate the level of patient satisfaction with the pharmacy services provided at the Primary Health Care Corporation’s (PHCC) pharmacies in Qatar. Methods. This study is a cross-sectional survey conducted in December of 2019. The study’s setting is the Primary Health Care centers’ pharmacies. All adult patients (≥18 years old) with mobile phone numbers documented on file… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
18
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(20 citation statements)
references
References 14 publications
1
18
1
Order By: Relevance
“…This is usually reflected through proper communication, patient‐centered decision‐making, and interpersonal style 40 . Good Communication skills were significantly related to high PS scores 13,20,22–24,26,27,29–32,34,36,38,39,41,42 . Patients' trust in the PC health provider to discuss private psychological health issues was found to positively affect their level of satisfaction 28,30,33 .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…This is usually reflected through proper communication, patient‐centered decision‐making, and interpersonal style 40 . Good Communication skills were significantly related to high PS scores 13,20,22–24,26,27,29–32,34,36,38,39,41,42 . Patients' trust in the PC health provider to discuss private psychological health issues was found to positively affect their level of satisfaction 28,30,33 .…”
Section: Resultsmentioning
confidence: 99%
“…Most of the older population were satisfied, 21,26,27,30,32,36,38,41 which they reported for physicians' rapport, 38 pharmacy services, 36 and the implementation of EMR 21 . However, a study showed dissatisfaction with physicians' services 29 .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Literature suggested that the development of communication skills should start at the undergraduate level and continue through the whole career of the dispensers. 35 The pharmacy schools and other training institutions in the country should allocate enough training time on dispensing practices and communication skills. In addition, dispensers should get on-the-job training through continuous professional development.…”
Section: Discussionmentioning
confidence: 99%